2014
DOI: 10.4161/15384101.2014.952973
|View full text |Cite
|
Sign up to set email alerts
|

Druggable glycolytic requirement for Hedgehog-dependent neuronal and medulloblastoma growth

Abstract: Aberrant activation of SHH pathway is a major cause of medulloblastoma (MB), the most frequent brain malignancy of the childhood. A few Hedgehog inhibitors, all antagonizing the membrane transducer Smo, have been approved or are under clinical trials for the treatment of human MB. However, the efficacy of these drugs is limited by the occurrence of novel mutations or by activation of downstream or non-canonical Hedgehog components. Thus, the identification of novel druggable downstream pathways represents a cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 33 publications
(46 reference statements)
0
37
0
Order By: Relevance
“…These characteristics strongly encourage the synergic therapy with itraconazole and ATO for the treatment of de novo Hh-dependent tumors or those with acquired resistance to cyclopamine [94]. Following these studies, the efficacy of ATO in targeting GLI transcription factors has been investigated in MB [93][94][95], pleural mesothelioma [96], malignant rhabdoid tumors [97], osteosarcoma [98], and many others cancer types. Furthermore, growing evidence points to a role for ATO as a modulator of the proliferation and differentiation of cancer cells progenitors by impacting on Hh or Notch signaling [99].…”
Section: Direct Gli Antagonists Gli Antagonist 61 (Gant61)mentioning
confidence: 96%
“…These characteristics strongly encourage the synergic therapy with itraconazole and ATO for the treatment of de novo Hh-dependent tumors or those with acquired resistance to cyclopamine [94]. Following these studies, the efficacy of ATO in targeting GLI transcription factors has been investigated in MB [93][94][95], pleural mesothelioma [96], malignant rhabdoid tumors [97], osteosarcoma [98], and many others cancer types. Furthermore, growing evidence points to a role for ATO as a modulator of the proliferation and differentiation of cancer cells progenitors by impacting on Hh or Notch signaling [99].…”
Section: Direct Gli Antagonists Gli Antagonist 61 (Gant61)mentioning
confidence: 96%
“…These evidence characterized that Shh overexpression was a critical event in breast carcinogenesis [8,9]. In addition, Shh activation induced transcription of hexokinase 2 (HK2) and pyruvate kinase M2 (PKM2) and caused a robust increase of glycolytic metabolism in medulloblastoma [10]. The process is mediated by the canonical activation of the Gli transcription factors [10].…”
Section: Introductionmentioning
confidence: 97%
“…In addition, Shh activation induced transcription of hexokinase 2 (HK2) and pyruvate kinase M2 (PKM2) and caused a robust increase of glycolytic metabolism in medulloblastoma [10]. The process is mediated by the canonical activation of the Gli transcription factors [10]. Nevertheless, the exact role of Shh signaling in breast cancer remains unclear.…”
Section: Introductionmentioning
confidence: 98%
“…Hh-dependent tumorigenesis and whether metabolic drugs may limit 586 Medulloblastoma growth wasn't addressed in that work. 587 We recently demonstrated that Medulloblastoma cells reprogram 588 glucose metabolism toward aerobic glycolysis mostly via the canonical 589 Gli-dependent pathway [131]. Furthermore, since aerobic glycolysis 590 can be targeted at multiple levels with specific drugs, we attempted to 591 understand if compounds that revert the glucose phenotype are also po-592 tential weapons against MB growth.…”
mentioning
confidence: 99%
“…Many of DCA ef-613 fects are linked to the inhibition of HIF1α transcription factor [137]. 614 Since DCA was used in patients with lactic acidosis and in clinical trials 615 of Glioblastoma, we tested its ability to counteract Hedgehog dependent 616 cell proliferation in preclinical models of Shh Medulloblastoma [131]. …”
mentioning
confidence: 99%